Video-based Learning of the Concept of Plant Tissue Culture during Covid19 among Higher Secondary Students : An Empirical Study - Balamurugan, M. (Voices of Teachers and Teacher Educators, 2023)
Plant tissue culture has great significance in plant biotechnology,especially in crop improvement. Video may have a positive impact on student performance in biology classes, as they find it more engaging. Enormous studies have shown that video can be a highly effective educational tool. Over the past few years, videos are being widely used in classrooms for supporting a curriculum and helping students learn the material faster than ever. The objective of this study was to improve the academic achievement in the concept of ‘Plant Tissue Culture’ among the Class 12 students through Video content in three parts with different strategies.The single-group test-retest experiment design was adopted for the study.The data were collected from Class 12 standard students of higher secondary school Thirunageswaram, Thiruvidaimarudur, Thanjavur, Tamil Nadu by the researcher for the study. The researcher took 17 (male 7 and female 10) as the sample size which was the total strength of the class 12 Biology stream.The magnitude of the difference between the pretest and posttest for achievement in ‘Plant Tissue Culture’ was estimated to be 2.893 through Cohen’s d effect size analysis, which was found to be very large.Thus it was clear that the video lesson with interaction gave a nearly five times better result than without any interaction and discussion. When the video was played in the classroom at a stretch students performed four times better than the video given as a home assignment. This research study has strengthened the argument that video can be a highly effective educational tool.